Pengaruh Corporate Social Responsibility terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening (Studi pada PT Bank Central Asia Tbk) - Surya Saputra; Abdul Hamid; Hendra Dwi Prasetyo (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the effect of Corporate Social Responsibility (CSR) on firm value with profitability as an intervening variable at PT Bank Central Asia Tbk during the 2020–2024 period. The research employed a quantitative associative approach using secondary data obtained from the company’s annual reports and sustainability reports. Samples were selected through purposive sampling based on the availability and completeness of CSR disclosure, profitability, and firm value data. CSR was treated as the independent variable, profitability as the intervening variable, and firm value as the dependent variable. Data analysis was conducted using descriptive statistics, classical assumption testing, multiple linear regression, partial hypothesis testing, and the Sobel test to evaluate the indirect effect. The empirical results show that CSR does not have a significant effect on firm value. Profitability also does not significantly affect firm value, while CSR does not significantly influence profitability. Furthermore, the Sobel test indicates that profitability is unable to mediate the relationship between CSR and firm value. These findings suggest that CSR activities undertaken by PT Bank Central Asia Tbk during the observation period have not been directly reflected in market valuation or short-term profitability. Investor assessments may be influenced more strongly by other factors, including business stability, risk management, growth prospects, and broader market conditions. The study provides evidence that the financial impact of CSR may require a longer observation period and more comprehensive measurement indicators.